AN ANALYSIS OF THE USE POSITIVE AND NEGATIVE POLITENESS BY NETIZENS ON ANIES BASWEDAN’S TWITTER ACCOUNT - Carolina Pakpahan; Galina Sitinjak; Tinadya Sinaga; Bertaria Sohnata Hutauruk (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2023)
Politeness is one of the phenomena found in daily communication. One of the studies of linguistics whose theory is pragmatic is called politeness. The objectives of this research to find out the politeness strategy and the percentage of the dominant type used by Indonesian netizents on Anies Baswedan Twitter. The research designed this study with qualitative method with the data from transcript of Indonesian netizents comment on Twitter. The findings show that: There are Bald on Record, Positive Politeness, Negativ Politeness, and Off Record. In twitter account there were 35 (33,65%) comments. In total, there are 2 (100%) Bald on Records, 13 (37,14%) Positive Politeness, and 9 (25,71%) Negative Politeness. The dominant type of Politeness Strategy used in Twitter accounts is Positive politeness. It takes 13 from 35 comments.